Histone modification of endothelial-mesenchymal transition in cardiovascular diseases - Jun, Qiu; Youhong, Li; Yuan, Zhong; Xi, Yang; Wang, Bingyu; Xinyi, Sun; Fu, Yin; Kedan, Cen; Lian, Jiangfang; Jianqing, Zhou (Frontiers in Cardiovascular Medicine, 2022)
Endothelial-mesenchymal transition (EndMT) is a differentiation process in which endothelial cells lose their own characteristics and acquire mesenchymal-like characteristics, which contributes to the formation and development of atherosclerotic plaques. Until now, there is still a lack of effective measures to treat atherosclerosis, so there is an urgent need to understand the underlying mechanisms of atherosclerosis. In addition, although various studies have shown that EndMT is involved in the pathological stages of cardiovascular diseases, such as myocardial fibrosis, myocardial hypertrophy, and hypertension, the specific molecular mechanisms driving EndMT are still in the exploratory stage. In addition, although various studies have shown that EndMT is involved in the pathological stages of cardiovascular diseases, such as myocardial fibrosis, myocardial hypertrophy, and hypertension, the specific molecular mechanisms driving EndMT are still in the exploratory stage. In this review, we review the role of histone modifications (methylation, demethylation and acetylation, deacetylation) on EndMT in cardiovascular disease, aiming to target histone-modifying enzymes to guide cardiovascular disease therapy.